Impediments Associated with Requirements in Agile Projects - Holmdahl, Fredrik (My University, 2020)
The agile principles does not lean on heavy documentation, and support changes by allowing changing requirements and even welcoming brand new during the development. Agile practitioners specify requirements on different abstraction levels, depending on the framework and personal preferences. Minimal documentation, no upfront requirements, and rapid working software are some of the luring traits of agile development. Terms like “just barely good enough” and “just in time” conflict with agile practitioners wanting more defined user stories and acceptance criteria. Organizations without existing agile knowledge can opt to outsource the development over applying internal education. Customers juvenile in agile development, a conflict of documentation levels in agile by different practitioners can cause challenges, such as customer availability, requirements lacking in detail, inappropriate architecture and contract conflicts. This study set out to identify and present these challenges and provide solutions related to agile requirements engineering in an outsourced environment. The data was gathered through a case study at a large consultant company. Interviews were used as the main source of collecting information, with the addition of forms. Related research was also included to relate the findings too, and collect any missing information not obtained from the case. The results are presented as impediments that hinder the project, accompanied by solutions on how to address them. The themes which include the impediments are lacking customer availability and engagement, insufficient architecture, requirements lacking in detail and customers lacking agile knowledge. Solutions are dedicated product owner, improved initial architecture, greater requirement detail and customer agile education.
Keywords: Agile; Scrum; Requirements Engineering; Impediments; Challenges; Solutions